2010
DOI: 10.1148/radiol.09091028
|View full text |Cite
|
Sign up to set email alerts
|

Does Multidetector CT Attenuation Change in Colon Cancer Liver Metastases Treated with90Y Help Predict Metabolic Activity at FDG PET?

Abstract: Changes in attenuation of colon cancer liver metastases treated with (90)Y radioembolization correlate highly with metabolic activity at FDG PET and may be useful as an early surrogate marker for assessing treatment response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 34 publications
1
14
0
1
Order By: Relevance
“…Choi and colleagues (9,10) have shown that changes in the attenuation of liver metastases from gastrointestinal stromal tumors after treatment with imatinib mesylate, a tyrosine kinase inhibitor, had higher sensitivity and specificity than anatomic imaging biomarkers in predicting response at fluorine 18 fluorodeoxyglucose positron emission tomography. Similarly, it has been shown that measurement of tumor attenuation change at CT improves the accuracy of assessment of response to yttrium 90 treatment in patients with liver metastasis and may help detect response to therapy earlier than size criteria alone (13). These reports underline the importance of an accurate Implication for Patient Care n Volumetry may be a better method of assessing change in tumor attenuation in response to therapy.…”
Section: Study Cohortmentioning
confidence: 95%
See 1 more Smart Citation
“…Choi and colleagues (9,10) have shown that changes in the attenuation of liver metastases from gastrointestinal stromal tumors after treatment with imatinib mesylate, a tyrosine kinase inhibitor, had higher sensitivity and specificity than anatomic imaging biomarkers in predicting response at fluorine 18 fluorodeoxyglucose positron emission tomography. Similarly, it has been shown that measurement of tumor attenuation change at CT improves the accuracy of assessment of response to yttrium 90 treatment in patients with liver metastasis and may help detect response to therapy earlier than size criteria alone (13). These reports underline the importance of an accurate Implication for Patient Care n Volumetry may be a better method of assessing change in tumor attenuation in response to therapy.…”
Section: Study Cohortmentioning
confidence: 95%
“…Narrower 95% limits of agreement were observed with the volumetric attenuation measurements. Change in attenuation of treated liver metastases may reflect response to therapy (13). In this study we did not evaluate the reproducibility of changes in attenuation measurements over time.…”
Section: Interobserver Reproducibilitymentioning
confidence: 96%
“…A recent study of patients with colorectal cancer liver metastases treated with TARE correlated the decrease in attenuation in the metastases with their appearances at FDG PET and demonstrated that changes in CT attenuation at 1 month after therapy may predict tumor response, as shown with FDG PET (24).…”
Section: Modified Ct Response Evaluation Criteria (Choi Criteria)mentioning
confidence: 96%
“…Moreover, lesion location and size are potentially influential on the reproducibility of ADC measurement [73]. ADC measurements in respiratory-triggered DWI are significantly higher and less reproducible than in breath-hold and free-breathing DWI [74].…”
Section: Morphological Changesmentioning
confidence: 99%